Preliminary study on the biological traits of the Por's goatfish Upeneus pori (Chordata: Actinopterygii) off the southern coast of Lampedusa Island (Central Mediterranean). Issue 1 (1st January 2018) - Geraci, M. L.; Scannella, D.; Falsone, F.; Colloca, F.; Vitale, S.; Rizzo, P.; Di Maio, F.; Milisenda, G.; Fiorentino, F.
Abstract: One hundred and six specimens of the Por's goatfish, Upeneus pori Ben-Tuvia & Golani (1989), a Lessepsian species native to the Western Indian Ocean, were collected from bottom trawlers' catches from 2012 to 2016 on the deep shelf off the southern coast of Lampedusa Island (Strait of Sicily, Central Mediterranean Sea). Since it first appeared in Iskenderun Bay (Turkey) in 1950, the Por's goatfish has quickly spread in Levantine Sea waters to become a commercial species used by local fisheries, while continuing its range expansion along the south-eastern coasts of the Mediterranean. Because the Strait of Sicily currently represents the westernmost sector of this species distribution area, it might serve as a stepping-stone for this species' expansion in the western basin of the Mediterranean. Supporting this hypothesis was our finding of specimens with post-spawning gonads. The pattern of westward expansion by the Por's goatfish in the Mediterranean Sea and its settlement in the Strait of Sicily are discussed in relation to the warming trend over the last 30 years.